CREATIVE ECONOMY DEVELOPMENT THROUGH PAINTING SKILLS AS AN INDICATOR OF THE LEVEL OF CREATIVITY OF CHILDREN WITH SPECIAL NEEDS SMA LB 1 BANTUL - Aisyah Astinadia Siregar (Jurnal Abdisci, 2024)
Creativity is possessed by children with special needs, also known as disabled children. He will show he is capable even though he knows he lacks. While discovering a child's identity, the support of parents and the environment is very beneficial. The Community Service Team can undoubtedly take advantage of this opportunity to help students with special needs of SMALB 1 Bantul in developing creative skills related to canvas painting. It is wise and wise to try to participate in special events to help children with special needs gain skills and enhance their creativity. In this painting activity, SMALB 1 Bantul students showed their creative abilities by painting on canvas.